CHARACTERISTICS OF STUDENT SELF EFFICACY AND ITS IMPLICATIONS FOR GUIDANCE SERVICES - Ade Lina Kirana; Nugraha, Agung; Isti’adah, Feida Noorlaila (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The research aims to get an overview of the self-efficacy characteristics of students who are in the process of completing their thesis at FKIP Muhammadiyah University Tasikmalaya. The background to this problem arises in the process of completing a thesis for students. The method used in this research is quantitative descriptive, involving 246 students who are in the process of completing their thesis at FKIP Muhammadiyah University Tasikmalaya. The data collection technique used in this research is an incidental sampling technique where anyone in the population can fill out a questionnaire by chance, and the data analysis method uses the calculation of averages, standard deviations, and percentages and tests for gender differences through SPSS 24.00. The results of the research show that the self-efficacy of students who are in the process of completing their thesis at FKIP Muhammadiyah University of Tasikmalaya tends to be in the high category with a score of 71%, the medium category is 29% and their is no self-efficacy in the low category or 0%. This research shows positive self-efficacy in the process of completing the thesis. Based on these findings, it is recommended that a role-playing technique group guidance service program be developed to develop student self-efficacy.